Promising Immunotherapy in Metastatic Testicular Sex Cord Stromal Tumours After First-Line Chemotherapy - Shang, Bingqing; Cao, Chuanzhen; Jiang, Weixing; Shi, Hongzhe; Bi, Xingang; Cui, Chengxu; Shou, Jianzhong; Zheng, Shan; Zhang, Jin; Zhou, Aiping; Li, Changling; Ma, Jianhui (Frontiers in Immunology, 2022)
Background Testicular sex cord stromal tumours (TSCSTs) are rare, with few studies focusing on the metastatic TSCST prognosis. The value of treatments, including radical orchiectomy (RO) and retroperitoneal lymph node dissection (RPLND), in preventing metastasis is controversial. Additionally, metastatic TSCSTs are resistant to chemotherapy. We aimed to assess the effectiveness and safety of immunotherapy in metastatic TSCSTs after first-line chemotherapy. Methods We retrospectively screened patients with testicular tumours undergoing testis surgery between January 2005 and January 2019. Patients with TSCSTs who had undergone testis-sparing surgery (TSS) or RO were identified. The malignant type was defined as metastasis confirmed by pathology. Treatment responses, progression-free survival (PFS), overall survival (OS) and safety were analysed. Results Among the 494 testicular tumour patients who received TSS or RO, 11 (2.2%) patients with histologically proven TSCSTs were identified. At the last follow-up, 7 patients survived without tumours, and 4 patients developed metastasis and received first-line cisplatin-based chemotherapy, with 1 of them achieving an objective response. Their PFS times were 1.5, 2.2, 9.0, and 17.0 months, respectively. Two patients received immune checkpoint inhibitors (ICIs) after developing chemotherapy resistance and achieved a partial response up to the last follow-up; one of them experienced Grade 1 adverse events, and the other experienced Grade 2 adverse events during immunotherapy. The median OS time of the 4 patients with metastatic TSCSTs was 32 months. Conclusions TSCSTs are rare, and most are benign with a good prognosis. ICIs represent a promising option for improving clinical outcomes in metastatic TSCSTs.